Subjective assessment of kinesitherapy as an element of comprehensive rehabilitation process of subjects with lower spine pain - Wioletta Łubkowska; Justyna Połeć; Mirosława Szark-Eckardt; Hanna Żukowska (Kazimierz Wielki University, 2016)
Łubkowska Wioletta, Połeć Justyna, Szark-Eckardt Mirosława, Żukowska Hanna. Subjective assessment of kinesitherapy as an element of comprehensive rehabilitation process of subjects with lower spine pain. Journal of Education, Health and Sport. 2016;6(2):255-266. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.46656 http://ojs.ukw.edu.pl/index.php/johs/article/view/3398 https://pbn.nauka.gov.pl/works/717132   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.01.2016. Revised 12.02.2016. Accepted: 21.02.2016.     Subjective assessment of kinesitherapy as an element of comprehensive rehabilitation process of subjects with lower spine pain   Łubkowska Wioletta¹, Połeć Justyna¹, Szark-Eckardt Mirosława², Żukowska Hanna²   ¹ Department of Physical Education and Health Promotion, University of Szczecin, Poland ² Kazimierz Wielki University in Bydgoszcz, Poland     Abstract Background. Spinal pain has triggered interest in many fields of medicine, such as orthopedics, neurology, rheumatology, and rehabilitation. Despite ongoing development of surgery techniques, a major role is played by fitness improvement treatments, which need to be promoted. The aim of the research was a subjective assessment of kinesitherapy as an element of comprehensive rehabilitation process of subjects with lower spine pain. Material/Methods. This paper has an empirical character. The research was conducted amongst a randomly selected group of 60 patients of Independent Public Health Care Unit in Choszczno, Poland (rehabilitation at an outpatients' clinic), aged 20-51. All of them were subjected to a series of 10 kinesitherapy treatments. The research used diagnostic polling method and the following techniques: survey and implicit interview. Results. The research proved that after completion of 10 treatments, the subjects noticed a significant improvement of their health. Kinesitherapy helped return to an active professional life for those who were forced to resign or suspend their work. Subjects reported that 10 kinesitherapy treatments were enough to notice their effectiveness in lumbar spine pain reduction. Kinesitherapy treatments resulted in a reduced usage of painkillers. Conclusions. There is evidence of positive impact of physical exercise on treatment results and beneficial effects in patients with spinal pain. Proper education aimed at changing bad habits and advising how to care for spine may be a powerful way to fight for health.   Keywords: spine, pain syndromes, lumbar spine, kinesitherapy, curative exercises, improving fitness.